Estimation of fertilizer use efficiency in vegetable systems using 15N: an overview - Laura Jalpa; Rao S. Mylavarapu (Discover Agriculture)
Abstract This overview focuses on the use of 15N labeled fertilizers to provide information about nitrogen (N) cycling processes in conventional vegetable production systems. Recent interest in determining fertilizer N use efficiency (FNUE) for vegetables may be due to the increase of global vegetable production, rise in N fertilizer costs, consumer preference for diversified plant-based diets, and interest in purchasing sustainably produced fresh foods. Vegetable production is known to require intensive amounts of N fertilizers, where the inefficiencies in N utilization can reach lower than 50%. To understand such systems comprehensively, the 15N technique was found helpful to investigate the co-factors involved in plant N uptake and identify sustainable solutions for economic vegetable production. Through a summary of the 15N studies, FNUE was found to range between 9 and 67%, with an average of 23% to 34%. Therefore, in most cases, over 70% of the applied N remained as residual or unaccounted for N in the soil post-harvest, which poses a significant risk for nitrate leaching and nitrous oxide emissions in vegetable systems. Despite advancements in production technologies, such as drip-irrigated plasticulture systems, inefficiencies persist due to excessive N fertilizer application and suboptimal timing of applications. While the cost of 15N-labeled fertilizers can be high, their use has provided critical insights into realistic N management scenarios, thus enhancing our understanding of important N transformation processes in vegetable systems. Additionally, the 15N natural abundance (δ15N) method facilitated the qualitative study of complex systems, where accurately labeling material such as enhanced efficiency fertilizers (EEFs), can be challenging with traditional 15N enrichment techniques. Further innovation of the 15N technique is necessary to study sustainable N management practices, including the use of EEFs, biochar, plant growth-promoting bacteria, and nitrification inhibitors, which are of increasing interest to the industry. Key takeaways from the 15N fertilizer studies emphasize the importance of improving N management strategies that optimize the source, placement, timing, and rate of N application to improve FNUE, minimize N pollution, and reduce reliance on economically prohibitive remediation approaches. This overview highlights the need for proactive and preventive N management strategies that reduce environmental impacts while enhancing the efficiency of vegetable production systems.